Study on Spatial–Temporal Evolution Characteristics and Restrictive Factors of Urban–Rural Integration in Northeast China from 2000 to 2019 - Yige Sun; Qingshan Yang (Land, 2022)
With the rapid development of urbanization and the widening gap between urban and rural areas, how to effectively enhance the balanced development of urban and rural areas as well as promote the integrated development of urban and rural areas have become heated topics. Based on the basic theory of urban–rural integration and spatial balance, this paper establishes a comprehensive evaluation system. Using a coupling coordination model and an obstacle degree model, this paper selects 32 indicators from aspects of economy, society and ecology to measure the development level of urban–rural integration in 34 prefecture-level cities in Northeast China from 2000 to 2019. We also analyze the spatial pattern, evolution type characteristics and obstacle factors of urban–rural relations. The results show that: (1) The growth rate of urban development in Northeast China is higher than that of rural development. Except for rural ecology, all dimensions of urban and rural areas have increased year by year, but there are large spatial differences within the region. (2) The urban–rural integration development level of Northeast China is growing constantly and the types of urban and rural coordination are all rising to a higher level. Areas with high urban–rural coordination levels are concentrated in the Harbin–Changchun urban agglomeration and the central and southern Liaoning urban agglomeration, with obvious agglomeration effects. (3) In the coordinated development of urban and rural areas, the restrictive degree of the rural social subsystem was higher than that of the urban subsystem. The restrictive factors in the coordinated development of urban and rural areas are relatively stable, and include per capita consumption expenditure, per capita public budget expenditure, books in public libraries per thousand people, etc. (4) The functions of rural social elements should be enhanced, and the social urban–rural integrated development mechanism should be established to promote the integrated development of urban and rural society.